(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Renewable energy sources are local sources, therefore they can improve the energy safety through reducing the demand for imported organic fuels, provide new employ-ment opportunities (particularly at small and medium –sized plants) and promote regional development. In this publication, an attempt was made of an analysis of the possibilities to create a sustainable development of rural areas based on the agricultural biogas plants.